2002
DOI: 10.1159/000067433
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Development of a Vaccine ‘Against Smoking’

Abstract: Background: Nicotine is the main culprit for dependence on tobacco-containing products, which in turn are a major etiologic factor for cardiovascular diseases and cancer. This publication describes a vaccine, which elicits antibodies against nicotine. The antibodies in the blood stream intercept the nicotine molecule on its way to its receptors and greatly diminish the nicotine influx to the brain shortly after smoking. Methods: The nicotine molecule is chemically linked to cholera toxin B as a carrier prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…Maximum titers were measured at about day 21 from which point antinicotine antibody levels slowly declined with a half-life of approximately 60 days. Addition of Alum increased the titers in mice about 6-fold and maximum titers after one boost (at day 14) were reached between day 40 and day 60. Analyses of the subclasses revealed high IgG2a titers which is indicative for a Th1-type immune response.…”
Section: Production and Immunogenicity Of Nicqbmentioning
confidence: 97%
See 3 more Smart Citations
“…Maximum titers were measured at about day 21 from which point antinicotine antibody levels slowly declined with a half-life of approximately 60 days. Addition of Alum increased the titers in mice about 6-fold and maximum titers after one boost (at day 14) were reached between day 40 and day 60. Analyses of the subclasses revealed high IgG2a titers which is indicative for a Th1-type immune response.…”
Section: Production and Immunogenicity Of Nicqbmentioning
confidence: 97%
“…The inhibition of nicotine entry into brain was analyzed by intravenous injection of tritium-labeled (-)-nicotine (Amersham) (739 ng or 1875 ng) in the tail vein and collection of blood and brain after five minutes. This time-point was selected because nicotine concentrations in the brain of mice decline with a half-life of about 6.5 min [14,31,32]. Nicotine concentrations in serum and brain were calculated from the radioactivity present.…”
Section: Animal Efficacy Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has shown in a mouse model that intranasal immunization is able to elicit significant levels of antibodies and we would expect some of the future application schedules to use intranasal application forms of the vaccine. 36 None of the vaccine studies carried out so far has reported major side effects. Some of the studies report on minor side effects, limited in most cases to the site of injection and which are of short duration.…”
Section: Further Developments To Expectmentioning
confidence: 99%